Altered lentiviral infection dynamics follow genetic rescue of the Florida panther. Issue 1913 (23rd October 2019) - Malmberg, Jennifer L.; Lee, Justin S.; Gagne, Roderick B.; Kraberger, Simona; Kechejian, Sarah; Roelke, Melody; McBride, Roy; Onorato, Dave; Cunningham, Mark; Crooks, Kevin R.; VandeWoude, Sue
Abstract : Wildlife translocations are a commonly used strategy in endangered species recovery programmes. Although translocations require detailed assessment of risk, their impact on parasite distribution has not been thoroughly assessed. This is despite the observation that actions that alter host–parasite distributions can drive evolution or introduce new parasites to previously sequestered populations. Here, we use a contemporary approach to amplify viral sequences from archived biological samples to characterize a previously undocumented impact of the successful genetic rescue of the Florida panther ( Puma concolor coryi ). Our efforts reveal transmission of feline immunodeficiency virus (FIV) during translocation of pumas from Texas to Florida, resulting in extirpation of a historic Florida panther FIV subtype and expansion of a genetically stable subtype that is highly conserved in Texas and Florida. We used coalescent theory to estimate viral demography across time and show an exponential increase in the effective population size of FIV coincident with expansion of the panther population. Additionally, we show that FIV isolates from Texas are basal to isolates from Florida. Interestingly, FIV genomes recovered from Florida and Texas demonstrate exceptionally low interhost divergence. Low host genomic diversity and lack of additional introgressions may underlie the surprising lack of FIV evolution over 2 decades. We conclude that modern FIV in the Florida panther disseminated following genetic rescue and rapid population expansion, and that infectious disease risks should be carefully considered during conservation efforts involving translocations. Further, viral evolutionary dynamics may be significantly altered by ecological niche, host diversity and connectivity between host populations.